Molecular tools in plant genetic resources conservation: A guide to the technologies - Karp, A.; Kresovich, Stephen; Bhat, K.V.; Ayad, W.G.; Hodgkin, T.; International Plant Genetic Resources Institute (1997)
In October 1995, IPGRI organized a small workshop on the use of molecular techniques in the conservation of plant genetic resources. One area of discussion was the considerable range of different molecular techniques available and the ways in which they could best be used. Deciding on which technique would be most appropriate for particular investigations is not always straightforward and depends on a range of a different factors including the nature of the problem, the biology of the species and the resources available. A number of the experts who participated in the meeting collaborated with IPGRI staff to prepare this publication, which attempts to provide a brief overview of currently available techniques and to outline some of their strengths and limitations. It also provides a framework to assist users in identifying what technique(s) might be most appropriate for their own needs. It is not intended as a laboratory manual of the techniques or as a substitute for the many excellent discussions of the strengths and weaknesses of individual methods that can be found in the literature. Rather, it is a broad survey of the main features of the different techniques and of the factors that conservation workers should bear in mind when initiating a molecular genetic based investigation.